(untitled) (Annals of Medical Research, 2021)
Aim: The aim of this regional study was to determine the frequency of physiological intracranial calcifications in all age groups in the province of Corum, to determine the relationship with age and gender, and through comparison with literature to present the basic data related to physiological intracranial calcifications. Materials and Methods: The study included 1011 patients aged 0-93 years that presented at the Emergency Department of Hitit University Medical Faculty Hospital because of head trauma and were applied with Brain Computed Tomography (BCT). A retrospective examination was made of the calcifications on BCT. The calcifications recorded on the CT scans were classified as choroid plexus, pineal gland, habenular commissure, dural, basal ganglia, and others. The patients were examined in 10 age groups of decades starting from zero. In this cross-sectional, retrospective, observational study, the relationship was examined statistically between age and gender of the patients and physiological intercranial calcifications. In addition, the prevalence values of physiological intercranial calcifications in the province of Corum were determined. Results: There was determined to be a statistically significant increase associated with increasing age in the frequency of pineal gland (p<0.001), choroid plexus (p<0.001) habenular commissure (p<0.001), dural (p<0.001), others (p=0.032) and basal ganglia calcifications (p=0.004). The rates of choroid plexus, pineal gland, and habenular commissure calcifications seen in males were determined to be statistically significantly higher in males than in females (p=0.044, p=0.033, p=0.032, respectively). Conclusion: This study determined the regional prevalence of physiological intracranial calcifications in the province of Corum and revealed the relationship between these calcifications with age and gender.